The Design of Youth Community Center in Bekasi City with a Behavioral Architecture Approach - Diaz Faiza Tawainella; Andi Purnomo; Hari Utama (Universitas Negeri Semarang, 2025)
Young people are a vital group in society who face various challenges during the important transition phase from age 15 to their early 30s. In this context, intensive attention and support are needed so that they can develop psychologically, socially, and economically. The Youth Community Center in Bekasi City is designed as a strategic solution to address these needs by creating a creative and collaborative space that supports the exploration of the interests, talents, and skills of young people. Given the rapid growth of the Bekasi City area, with its high level of urbanization, the emphasis on providing facilities that support creativity and innovation is crucial. With the Behaviour Architecture approach, the Youth Community Center is expected to stimulate social interaction and productivity so that it functions not only as a gathering place, but also as a catalyst in facilitating the potential and overcoming the challenges faced by the younger generation in Bekasi City. In the design of the Youth Community Center in Bekasi City using the Behavior Architecture approach, the data used consists of primary and secondary data, which is then analyzed using 5 aspects of the approach, including the functional approach, contextual approach, technical approach, performance approach, and architectural approach. The results of the architectural design aspects that have been analyzed then become guidelines for the next design process.